Pelatihan Analisis Instrumen Menggunakan Quest untuk Meningkatkan Kompetensi Guru dalam Evaluasi Pembelajaran - Tumanggor, Awal Mulia Rejeki; Ahmad, Liza Septia; Sekeon, Cristi Ascika; Silaban, Yohansen Frando Hadinata; Pujianti, Isna; Tarigan, Yustinus (Jurnal Inovasi Pengabdian Masyarakat, 2026)
This community service activity aimed to improve teachers' competency in analyzing learning evaluation instruments through training on Quest software based on the Rasch Model. The participants were 25 high school teachers in Tondano, conducted online via Zoom over two days using a participatory training approach. The method included preparation, execution (conceptual reinforcement, demonstration, hands-on practice, and reflective discussion), and evaluation stages. Data were collected through pretests-posttests, questionnaires, and observations, then analyzed descriptively. Results showed a significant increase in competency, with the average pretest score of 46.80 increasing to 81.20 on the posttest (a 73.50% increase). The N-Gain value of 0.65 falls into the medium category, indicating meaningful training effectiveness. A total of 92% of participants showed substantial improvement and were able to operate Quest and interpret outputs such as item difficulty (logit), item fit statistics (INFIT/OUTFIT MNSQ), and reliability. Participant responses were very positive, with 88% stating the material was relevant and 84% committing to apply the training results in their schools. This activity contributes to strengthening teachers' pedagogical competence in evidence-based learning evaluation.